Real democracy : the New England town meeting and how it works - Bryan, Frank M. (American politics and political economy., 2004)
"Relying on more than three decades of firsthand research, Frank M. Bryan examines one of the purest forms of American democracy, the New England town meeting. At these meetings, usually held once a year, all eligible citizens of the town may become legislators; they meet in face-to-face assemblies, debate the issues on the agenda, and vote on them. And although these meetings are natural laboratories for democracy, very few scholars have systematically investigated them." "Studying 1,500 towns in his home state of Vermont, Bryan and his students recorded a staggering amount of data about them. Drawing on this evidence as well as on evocative "eyewitness" accounts, Bryan paints a vivid picture of how real democracy works. In the end, Bryan interprets this brand of local government to find evidence for its considerable staying power as the most authentic and meaningful form of direct democracy."--Jacket.